1997
DOI: 10.1104/pp.113.4.1293
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Immunological Identification of Metallothioneins 1 and 2 from Arabidopsis thaliana

Abstract: Gene families encoding two types of metallothioneins (MTs), MT1 and MT2, have been identified in Arabidopsis thaliana, and their respective mRNAs have been shown to be regulated by copper in a tissue-specific manner (J. Zhou and P.B. Goldsbrough [1994] Plant Cell 6: 875–884; J. Zhou and P.B. Goldsbrough [1995] Mol Gen Genet 248: 318–328; A.S. Murphy and L. Taiz [1995] Plant Physiol 109:1–10). However, to date the protein products have not been identified. To purify MT proteins from Arabidopsis, we isolated low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 36 publications
3
117
0
8
Order By: Relevance
“…Here we have demonstrated that six Arabidopsis MTs, including representatives of all four types of plant MTs, can impart metal tolerance when expressed in S. cerevisiae. Although the metal-binding capacity of some plant MTs has been previously demonstrated (Tommey et al, 1991;Evans et al, 1992;Murphy et al, 1997), this is the first report, to our knowledge, to compare all four types of MTs from a single plant species. Our results suggest that all MT isoforms are able to bind Cu ions in vivo.…”
Section: Discussion Arabidopsis Mts Can Impart Metal Tolerance In Vivomentioning
confidence: 86%
See 1 more Smart Citation
“…Here we have demonstrated that six Arabidopsis MTs, including representatives of all four types of plant MTs, can impart metal tolerance when expressed in S. cerevisiae. Although the metal-binding capacity of some plant MTs has been previously demonstrated (Tommey et al, 1991;Evans et al, 1992;Murphy et al, 1997), this is the first report, to our knowledge, to compare all four types of MTs from a single plant species. Our results suggest that all MT isoforms are able to bind Cu ions in vivo.…”
Section: Discussion Arabidopsis Mts Can Impart Metal Tolerance In Vivomentioning
confidence: 86%
“…It has been shown that MT1 and MT2 proteins from Arabidopsis can be purified by Cu affinity chromatography and are able to bind Cu ions in vitro (Murphy et al, 1997). When expressed in the yeast Dcup1 mutant, the MT1a and MT2a genes were also able to confer Cu and Cd tolerance (Zhou and Goldsbrough, 1994).…”
Section: Arabidopsis Mts Are Functional Chelators Of Cu and Zn In Vivomentioning
confidence: 99%
“…MTs bind to Cu, Cd and Zn; they probably regulate intracellular Zn concentrations and detoxify normally lethal concentrations of Cd and Cu (Murphy et al, 1997). MTs have the highest a nity to Cu, and MT expression correlates with Cu but not Cd tolerance in Arabidopsis (Murphy and Taiz, 1995).…”
Section: Mts and CD Tolerancementioning
confidence: 99%
“…For plant, MTs can efficiently bind metals (Murphy et al, 1997;Leszczyszyn et al, 2007) and some of them are transcriptionally regulated by metals; they are also thought to play important roles in metal tolerance, detoxification, and homeostasis in plants (Cobbett and Goldsbrough, 2002;Hall, 2002;Hassinen et al, 2007). On the other hand, there were also intensive studies for the responses of MTs to stress conditions, such as draft and reactive oxidant species (Akashi et al, 2004;Wong et al, 2004).…”
mentioning
confidence: 99%